Dilution effects on aggregates and filaments contents in automated image analysis methodologies - Dias, Oscar (2008)
Monitoring activated sludge processes by microscopic observations and image analysis is a well established technique with the utmost importance for microbial community characterization. Occasionally, there are biological systems operating with high biomass concentrations that need to be diluted, causing reproducibility problems for the sampling and image analysis methodologies. In the current work, image processing and analysis methodologies were used to determine the aggregates and filamentous bacteria contents and morphological characterization, of five dilutions from three activated sludge systems. The outcome of reducing the concentration of the samples was obtaining almost 3.5 times the pattern results for the total filamentous bacteria contents and almost the double for the total aggregates contents. Moreover, the differences were diverse for each aggregates class and, therefore, the dilution effects cannot be predicted and quantified for all of the aggregated biomass as a whole based on an overall correction factor.